How May China Respond to the U.S. Trade Approach? Retaliatory, Inclusive and Regulatory Responses - Wang, Heng (Columbia Journal of Asian Law, 2018)
This paper endeavours to conceptualize and provide an analytical framework for China’s response to U.S. trade policy. It analyses the following questions: what is the new U.S. trade approach? How might China respond to the United States’ trade approach? What are the trend and implications of China’s response to the U.S. trade approach? It argues, first, that the U.S. trade approach has not changed regarding most of the U.S.-style regulatory disciplines. However, it has changed in terms of the shift toward managed trade, unilateralism and trade enforcement. Second, China will likely adopt a three-track approach: consisting of retaliatory, inclusive and regulatory responses. Third, these responses exist on a political-legal spectrum that spans from a more political retaliatory response through to an inclusive one, or a more legalized approach (regulatory response). The inclusive response is likely to be given primacy by China over the other two responses, and China’s responses carry profound implications.